Profiles of Dialogue for Amphiboly - Walton, Douglas (Informal Logic, 2020)
Amphiboly has been widely recognized, starting from the time of Aristotle, as an informal fallacy arising from grammatical ambiguity. This paper applies the profiles of dialogue tool to the fallacy of amphiboly, providing a five-step evidence-based procedure whereby a syntactically ambiguous sentence uttered in a natural language text can be evaluated as committing a fallacy of amphiboly (or not). A user applies the tool to a natural language text by comparing a descriptive graph, representing how the argumentation actually went, to a normative graph, representing how the argumentation should ideally have proceeded.